Social inclusion for whom and towards what end? A critical discourse analysis of youth and sport policies in Turkey - AŞÇI, FEVZİYE HÜLYA (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This article examines the social inclusion policy strategies of the Turkish Ministry of Youth and Sport (MYS). Using a critical discourse analysis, based on Norman Fairclough's work (2012), the aim is to analyse the discourses used within policy-related documents regarding social inclusion, youth, and sport. In order to achieve this objective, we analysed 15 key documents, including annual activity reports, national youth and sport policy documents, and strategic plans produced by the Ministry. Findings revealed that the dominant discourses about young people seem to be embedded within neoliberal and neoconservative ideologies in which depoliticised notions of 'employment/apprenticeship' and 'the family' are put forward as solutions for the social inclusion of young people. However, such a discourse risks further sustaining the social exclusion of youth, denying their full citizenship.
Keywords: Youth; social exclusion; sport; unemployment; critical discourse analysis; NEOLIBERALISM; GENERATION; STATE; POWER